3D Virtual reconstruction of asphalt mixture microstructure based on rigid body dynamic simulation. Issue 1 (6th December 2023) - Han, Dongdong; Xi, Yinfei; Xie, Yichang; Li, Zhaocheng; Zhao, Yongli
ABSTRACT: This paper presents a virtual generation method for the heterogeneous microstructure of asphalt mixtures. The coarse aggregates used in the digital asphalt mixture were derived from real aggregates captured by a three-dimensional (3D) laser scanner. Then, a rigid-body dynamic simulation framework was proposed to generate a stable skeletal structure composed of coarse aggregates similar to those formed by compaction. Furthermore, FAM and air voids were generated based on the generated aggregate skeleton and the assumption of equal thickness of FAM film. To prove the reliability of the model, the air voids of the digital asphalt mixture samples were verified by comparison with real specimens. The generated digital specimens were also applied to finite element method (FEM) simulations to predict the dynamic modulus of the asphalt mixture and the simulated results were in good agreement with the experimental results. The method can be applied to study the spatial distribution of asphalt mixture components, the movement pattern of aggregate particles during compaction and numerical simulations at the microscopic scale.